Wimbledon - Bevan, Tim.; Fellner, Eric.; Chasin, Liza.; Richards, Mary.; Brooks, Adam 1956-.; Flackett, Jennifer; Levin, Mark R. (Mark Reed) 1957-.; Loncraine, Richard; Dunst, Kirsten 1982-.; Bettany, Paul 1971-.; Neill, Sam.; Favreau, Jon.; et al. (Universal City, Calif. Universal, 2004)
An aging male tennis star has one last shot, and two weeks, to win the greatesst tennis tournament and the heart of an upcoming women's tennis star.
Special features: Wimbledon : a look inside; welcome to the club; ball control; coach a rising star; feature commentary with Paul Bettany and Richard Loncraine; theatrical trailer.
Director of photography, Darius Khondji ; editor, Humphrey Dixon ; music, Edward Shearmur ; costume designer, Louise Stjernsward ; production designer, Brian Morris.
Kirsten Dunst, Paul Bettany, Sam Neill, Jon Favreau, Bernard Hill, Eleanor Bron, Nikolaj Coster-Waldau, Austin Nichols, Robert Lindsay.
MPAA rating: PG-13; for language, sexuality and partial nudity.
DVD, region 1; Dolby Digital 5.1, DTS 5.1 surround.
English or French dialogue with optional French or Spanish subtitles; closed-captioned.
Keywords: Tennis players -- Drama; Man-woman relationships -- Drama; Feature films; Video recordings for the hearing impaired